The impossible woman and sexist realism on NBC's Parks and Recreation. Issue 4 (2nd October 2021) - Hoerl, Kristen
ABSTRACT: This article critically interprets the NBC television program Parks and Recreation, analyzing its main character Leslie Knope as emblematic of an emerging rhetorical figure in public culture: the impossible woman. The impossible woman informs the possibilities for subjectivity and political engagement among audiences drawn to feminist messages as it mediates between the competing demands of feminism and neoliberalism through narrative structures that evoke what I have termed sexist realism, the presumption that, strive as we must to resist it, there is no alternative to patriarchy. I explore how the impossible woman is at once a product of and response to sexist realism as popular feminist rhetoric has made a virtue of feminist striving. The proliferation of the impossible woman in public culture celebrates this feminist virtue even as it cannot imagine collective feminist outcomes.